Lexis Expansion: a prerequisite for analyzing time changing variables in a cohort study - Nitika, Nitika; Mishra, Sidharth Sekhar; Lohani, Pallavi (Nepal Journal of Epidemiology, 2017)
In a prospective analytical cohort study or a study involving a longer follow up, changing age of participants influence the relationship between exposure and outcome. Usually age at entry is incorporated in the regression model to adjust for age. However, this fails to fully explain and adjust for changing age. For this Lexis expansion, a concept by Wilhelm Lexis, allows the analyst to expand the observations as per age bands and check for confounding and interaction by changing age. Lexis expansion assumes the rates to be constant within an age band.